Pelatihan dan pendampingan pemasaran digital bagi Apotek Taman Sari dan Toko Rindang Pasar Raya 1 Salatiga - Elisa Amalia Triananda; Jerry Christian Batubara; Sotya Fevriera; Angelita Titis Pertiwi; Christina Ari Pramono Putri (Nur Science Institute, 2026)
MSMEs play a vital role in the economy. However, the number of MSMEs in Salatiga that have adopted digital marketing is still not comparable to the number of consumers who have adopted digital payments. This community service activity aims to provide digital marketing training to merchants mentored by the Salatiga Trade Office, assist two merchants in developing their digital marketing through social media, and help them create at least three pieces of digital marketing content. The activity consists of four stages: training, activity socialization, merchant profiling, and digital marketing development. The final two stages were conducted using a Participatory Action Research approach. The mentoring resulted in the creation of a professional Instagram account for the business, a Google Maps, a booklet, and two videos to be uploaded to Instagram. The mentoring also taught merchants how to upload photos and provide price tags to promote their products. Thus, the objectives of the community service activity have been achieved.